Knowing work : the social relations of working and knowing - Weil, Markus [Mitarbeiter]; Koski, Leena [Mitarbeiter]; Mjelde, Liv [Mitarbeiter]; Daly, Richard [Mitarbeiter]; Gamble, Jeanne [Mitarbeiter]; Shore, Sue [Mitarbeiter]; Lukas, Norman [Mitarbeiter]; Roldán, Martha [Mitarbeiter]; Jorgensen, Christian Helms [Mitarbeiter]; Siecke, Bettina [Mitarbeiter] (Lang, 2009)
"This book discusses new contradictions in the processes of vocational education. It poses questions on how today's knowledge is to be taught and what should be learned within vocational education. The meanings of work, the characteristics of knowledge and knowing, and the processes of vocational learning and educating are complex in contemporary societies. The vocabularies, discourses, and policies are changing globally. Coexisting and contradictory processes, practices, ideas, and ideals shift, waver, and then take hold. It is difficult to understand how they relate to their societies and to the lives of human beings. The neo-liberal policies governing the relations between capital and labour - the state and the labour market - severely affect both the changing and unchanging features of working and learning. The book approaches vocational education from three perspectives: moral and symbolic orders that are embedded in cultural and social relations, working and knowing at school and at the work place, and the dynamic combination of knowing and working as these are experienced within the ideas and practices of vocational education." (Verlag, BIBB-Doku)
Keywords: G 2.2.2 Internet / Mediengesellschaft; G 2.3.4 Qualifikationswandel; G 2.4 Sozialer Wandel; Berufsbildung; Wissensgesellschaft; Wissensarbeit; Wissensmanagement; Lernform; Lernende Organisation; Soziale Beziehungen